Comparison of scoring tools EMSE and STESS for the prediction of in-hospital mortality in convulsive status epilepticus in adults and the elderly - Verma, Archana; Kumar, Alok; Kumar Verma, Manoj (Nepal Journal of Neuroscience, 2022)
Aim: The aim of this study was to compare the predictive accuracy of the Status Epilepticus Severity Score (STESS) and the Epidemiology-based Mortality Score in Status Epilepticus—etiology, age, and levels of consciousness (EMSE-EAL) score for in-hospital mortality in adults and the elderly with CSE. Methods: We conducted a hospital-based cross-sectional study. A total of 193 participants with a diagnosis of CSE were enrolled in the study. The means area under the receiver operating characteristic curve (AUC) was compared to distinguish between the score performances. Results: The average age of the respondents was 46.15 ± 20.25 years; 138 (69.8%) of them were adults, and 55 (30.2%) were elderly. In our study, in-hospital mortality was 30 (15.5%). In adults, on comparison STESS with the cutoff value of ≥3 has an AUC of 0.712 (95 percent CI =0.60–0.83), whereas ESME-EAL with the cutoff value of ≥40 has an AUC of 0.912 (95 percent CI =0.86–0.97), and in the elderly, STESS has an AUC of 0.613 (95 percent CI =0.43–0.80), and ESME-EAL has AUC of 0.848 (95% CI =0.74–0.80). Conclusions: The EMSE-EAL-40 score is superior to the STESS-3 for predicting in-hospital mortality in both adults and the elderly with CSE. EMSE-EAL can be easily applied in resource-poor sectors with constrained diagnostic facilities.